Franz Schubert und Moritz von Schwind - Göltl, Reinhard,Schubert, Franz,Schwind, Moritz von (Nymphenburger, 1989)
Literaturverzeichnis
Includes bibliographical references (p. 147) and indexes
Keywords: Schubert; Franz; Schwind; Moritz von